Digital Media Management Strategy by Local Governments In Tourism Marketing - Femmy Indriany Dalimunthe; Liyushiana Liyushiana; Dewi Yanti; Mohammad Yusuf Dalimunthe; Mbaze-Ebock Vivian Arrey (LPPM Universitas PGRI Sumatera Barat, 2025)
This Phenomenon provides opportunities to utilize the internet and social media in various business sectors, including marketing activities that are usually carried out in the tourism industry. This study was conducted to formulate a digital media management strategy in tourism marketing by local governments. This study was conducted in the city of Medan, where local officials have attempted to utilize various digital media platforms in tourism marketing. Unfortunately, tourists are less enthusiastic about visiting events and tourist attractions in this city. Therefore, it is necessary to reanalyze the existing conditions by formulating new strategies for digital tourism marketing by the Medan City Tourism Office. This study was conducted using PEST analysis, Porter’s Diamond Model, Value Chain Analysis, SWOT Analysis, and Balanced Scorecard. The results identified 8, 16, 13, and 4 categories of strengths, weaknesses, opportunities, and threats. The SWOT analysis results place digital media tourism marketing in quadrant III. The conclusion from the results and discussion is that strategy mapping and measurement using the Balanced Scorecard categorizes 13 alternative strategies into 4 perspectives, namely financial, customer, business process, and growth and learning. The novelty of this research is that the growth and learning perspective produces two alternative strategies, namely conducting market analysis and designing target profiles for each platform